Mapping The Characteristics of Medical Influencer on Social Media: A Study from Indonesia - Ernungtyas, Niken Febrina; Boer, Rino Febrianno; Femmy, Femmy (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
Social media have a crucial role in health discourse and have become a health information source in Indonesia. Health professionals have actively shared information, updated the situation and regulations, explained the cases by answering users’ questions, and combated the hoax through their accounts during the COVID-19 pandemic. Health professionals are still perceived as credible and trusted sources to provide health information and messages to the public. This study aims to describe the credibility and expertise aspect of a medical doctor on social media, particularly Instagram, TikTok, and Twitter. The research uses a quantitative approach capturing the bio and content from the accounts of medical influencers. The research findings reveal that health professionals on social media have transformed into microcelebrities, where some receive pay to promote and self-promote themselves.